The Effectiveness of Using a Cognitive Style-based Chatbot in Developing Science Concepts and Critical Thinking Skills among Preparatory School Pupils - Suzan Samir Barsoum; Mohamed S. Elnagar; Boushra Mossad Awad (European Scientific Journal, ESJ, 2022)
The research investigated the effectiveness of using a cognitive style-based chatbot in developing science concepts and critical thinking skills among preparatory school pupils. To achieve the aim of the research, the researchers applied the two groups' quasi-experimental design and utilized three instruments as follows;1) Budner scale to measure the tolerance of ambiguity; 2) Science concepts achievement test developed by the researchers and implemented before and after applying a cognitive style-based chatbot; 3) The critical thinking skills test developed by the researchers to identify four critical thinking skills required for grade 8 level and implemented before and after applying a cognitive style-based chatbot. The participants were chosen randomly from eighth-graders (N=50) at HOIS (Hurghada Official International School), Red Sea Governorate, Egypt. The researchers divided participants into two experimental groups of 25 pupils (EGA) and (EGB) according to their cognitive style as tolerant or intolerant of ambiguity. Quantitative results showed the significant mean differences between the scores of participants at level (0.005 ≥) in the pre-post testing procedures in favor of the post-testing for both dependent variables (science concept and critical thinking skills). Results indicated the positive impact of utilizing a cognitive style-based chatbot in developing science concepts and critical thinking skills for preparatory school pupils. So, the researchers recommended employing chatbots in learning science for their high effectiveness in developing science concepts and critical thinking skills among preparatory school pupils in Egypt.